Electronic Properties of Amyloid β‐Based Peptide Filaments with Different Non‐Natural Heterocyclic Side Chains. Issue 5 (6th April 2014) - Amit, Moran; Ashkenasy, Nurit
Abstract The incorporation of non‐canonical amino acids with aromatic side chains is considered to be a promising way to improve and control the electronic properties of self‐assembled peptide nanostructures. In this work, we have studied the influence of aromatic ring heteroatom on the electronic properties of amyloid β‐derived peptide fiber networks. We show that the incorporation of furan instead of thiophene side chains results in only small changes in the resistivity of the peptide network, with a threefold increase in the sheet resistance and a small decrease in the contact resistance. These changes can be explained by a twofold decrease in the diameter of the self‐assembled fibers. These characteristics open the way to the use of furan‐ instead of thiophene‐based analogues as non‐natural side‐chain modifications of peptides for electronic applications; this makes the fibrils more biodegradable and biorenewable.